A inclusão da variável climática no processo de licenciamento ambiental: uma breve análise da realidade do Estado de São Paulo. - Fábio Takeshi Ishisaki (Confins)
Business activities are of considerable importance in modern society, whether in the economic, social or environmental sphere. Therefore, there is a need for these activities to adapt to urgent global issues, among which those related to the environment and, notably, climate change deserves to be highlighted. Emissions analyzes carried out by international and national organizations demonstrate the importance of the climate issue in human activities and, especially in Brazil, of the contributions of several states to GHG emissions. Thus, the objective of the present study is to trace a history of the inclusion of the climate issue in the Brazilian environmental licensing, in view of its importance in making feasible business activities of great climatic impact. For that, the official data and reports from the IPCC, the Brazilian Government and research entities were consulted, as well as the bibliographic production and legislation applicable to the theme. Based on this information, the problem of the lack of inclusion of the mandatory measurement of greenhouse gas emissions in environmental licensing will be demonstrated, specifically in the state of São Paulo. Given the relevance of the state of São Paulo in the national PIB and in the emissions of GHG, the present study was based on official documents from organizations such as the IPCC, the Brazilian GHG Protocol Program and CETESB, in addition to Brazilian legislation, seeking to analyze the models currently in force in Brazil and in the state of São Paulo, notably regarding the inclusion of the climate variable when environmental licensing. It was found, therefore, that although required in climate policies, there is no normative requirement for analyzing issues related to GHG emissions in the environmental licensing process in the state of São Paulo.